Cognition and biomarkers of oxidative stress in obstructive sleep apnea (Clinics, 2013)
OBJECTIVES: The aim of this study was to investigate neuropsychological performance and biomarkers of oxidative stress in patients with obstructive sleep apnea and the relationships between these factors. METHODS: This was an observational, cross-sectional study of 14 patients (36.0±6.5 years old) with obstructive sleep apnea and 13 controls (37.3±6.9 years old). All of the participants were clinically evaluated and underwent full-night polysomnography as well as neuropsychological tests. Blood samples were used to assay superoxide dismutase, catalase, glutathione and homocysteine, as well as vitamins E, C, B11 and B12. RESULTS: The patients performed poorly relative to the controls on several neuropsychological tests, such as the attention test and tests of long-term memory and working memory/executive function. They also had lower levels of vitamin E (p